Resilience of Fishery Economy in Fujian Coastal Areas from the Perspective of Institutional Evolution - Leng Yun; Wei Suqiong; You Xiaojun; Ren Zhihuang (Redai dili)
This study considers the fishery industry in the coastal area of Fujian Province as an example, measures the resilience resistance of the fishery industry using output value and output, and constructs an analytical framework by combining the "Robustness-Resistance-Recovery" resilience assessment framework and the theory of institutional change to give explanations for the formation of the differences in fishery resilience. The four types of gradually deepening institutional changes are layering (thickening and positive layering), conversion, and displacement. The robustness dimension of resilience corresponds to thickening, the resistance dimension corresponds to positive layering, and recovery corresponds to conversion or displacement. Three main conclusions are drawn: 1) Under the influence of different types of shocks (the super-typhoon in 2006, the financial crisis in 2008, and the upgrading of the fishing industry in 2017), the output value fluctuates significantly owing to the dual effects of production and supply, and the output is more strongly affected by production and more drastically reflective of natural disasters. 2) A spatial regularity exists in the impact of regional crises (typhoons) on industrial resilience resistance; the closer to the disaster center, the poorer the performance of industrial resilience resistance. The economic and industrial transformation crises have a homogeneous effect on the fishery economy, and the spatial differences in the resilience of the fishery economy are more influenced by historical foundations and institutional evolution. 3) The 25 research units in coastal areas were divided into five categories. The spatial distribution of fishery resilience is affected by coastline length. High-resilience areas were mainly concentrated in the middle of the coastal region in the study units with longer coastlines. The resilience of the north and south ends improved from year to year, and the length of the coastline in the areas with lower resilience was shorter. Differences were noted in the performance of each region in terms of resilience to shocks, including robustness, resistance, and resilience, as well as differences in the depth of institutional change types. Regions that choose the right development path and the right mode of institutional change in a crisis are more resilient and help the region reduce resource constraints on fisheries development, even if it is a thickening of the original system that can defuse the crisis, whereas a few regions are less resilient in choosing a direction of institutional change that is separatedfrom the region's industrial base, where new development paths have yet to take root. This study highlights the importance of regional institutional change in the formation of fishery resilience, provides a new perspective on how institutional change affects economic activity, and uses quantitative methods to investigate the relationship between institutional change and industrial resilience. In addition, this study has important implications for disaster response and risk management, helping firms and governments better prepare for and respond to potential economic shocks.